EFILING INFORMATION SYSTEM OF VILLAGE DOCUMENTS WEB-BASED CASE STUDIES BANGUN VILLAGE-PUNGGING - Yeni Kurnia Wati; Ika Ratna Indra Astutik (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2017)
Efiling village information system is a collection of software and computer hardware and human devices that will process archival data in the form of village documentation systematically so that when needed again can be found again quickly which will be needed Bangun village. Archiving of the Bangun village is still manual and its layout is hard to remember in the long run when needed. The purpose of this study is to facilitate the admin, staff and the community in data archiving, data search and reminder functions in personal identity renewal and payment of land and building tax effectively and efficiently. Efiling system is designed by using PHP programming language and MySQL database consisting of 3 permissions by admin, staff, and community. This system works by scanning incoming data to be archived and stored in the village admin database and can be seen through the android community. The result of this application is to archive personal letters of citizens and as a function of reminder when personal letter updates and efficient tax payments. From the results of the application test found that 91% of applications run well.